RESOURCE BASED LEARNING FOR TEACHING ARABIC - Awaludin, Awaludin (Ijaz Arabi Journal of Arabic Learning, 2019)
The teaching process requires new creativity and ideas to develop ways of presenting subject matter at school. The teacher must carefully choose the approach or teaching methods so that the objectives of the learning outcomes can be achieved. One model used is through the Resource Based Learning Model. The purpose of the study was to determine the implementation and influence of the Resource-Based Learning Model in improving student learning outcomes in Arabic. This research is a classroom action research conducted in 3 cycles. The results of the study show that students' abilities increase by achieving ideal standards. From 56.89% in Cycle l, it can increase to 67.27% in cycle II, and cycle III increases to 77.24%. This shows that the application of the Resource-Based Learning Model can effectively improve students' Arabic learning outcomes